Poor correlation between clonal immunoglobulin gene rearrangement and immunoglobulin gene transcription in Hodgkin's disease. - Yatabe, Y. (1996)
It recently has been suggested that some cases of Hodgkin's disease (HD) are derived from B lymphocytes. We therefore examined immunoglobulin heavy chain gene rearrangement and transcription by polymerase chain reaction in 30 cases of HD and compared them with 25 cases of non-Hodgkin's B-cell lymphoma. Clonal VDJ gene rearrangements were observed in 6 cases of HD. Of these 6 cases, clonal VDJ gene transcription was found by RNA-dependent polymerase chain reaction in only 2 cases. One of these 2 cases histologically showed composite lymphoma of HD and diffuse large B cell lymphoma. We performed in situ hybridization with a clonal VDJ gene probe in this case to determine the localization of the genetic clonality. The large lymphoma cells reacted positively, but Hodgkin's and Reed-Sternberg cells showed only nonspecific staining. No discrepancy between immunoglobulin gene rearrangement and transcription was observed in 24 of the 25 cases of non-Hodgkin's B-cell lymphoma. The discordance between clonal gene rearrangement and transcription in HD contrasts sharply with the high correlation of those processes in non-Hodgkin's B-cell lymphoma.